(untitled) (Journal of Parents and Teachers, 2012)
This paper explains, in a didactic and clear way, the theory of emotions of the teacher Leslie Greenberg and, also, justifies the need of future teachers of receiving a theorical and practical training that can help them to develop their socio-emotional competences. In particular, the author of this article points out the elaboration of a emotional diary that their students of second grade of infant education and primary education of the degree of Teaching of the Universidad Pontificia de Comillas write in the cuatrimestral course. Readers could find a definition of the six basic emotions and, also, the definition of shame and help about how to manage our own emotions being able to identify if they are adaptive or desadaptive primary emotions or secondary or instrumental emotions. ions being able to identify if they are adaptive or desadaptive primary emotions or secondary or instrumental emotions.